2022
DOI: 10.7759/cureus.28336
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Attitudes, Knowledge, and Beliefs about Medical Cannabis: A Qualitative Descriptive Study

Abstract: BackgroundThere has been increased attention given to understanding the uses of medical cannabis (MC) for symptom management of various medical conditions. Physicians receive minimal training in medical school and rely mostly on anecdotal evidence; by proxy, medical students generally do receive formal training in MC. It is unknown how medical students perceive MC, including its efficacy, appropriateness in medicine, its possible adverse effects, and its value for patients. This study investigated medical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Specifically, greater self-assessed knowledge of psilocybin, more concern for possible negative effects from its use, and greater belief in the decriminalization of psilocybin for both recreational and therapeutic use were significant predictors of more positive attitudes about psilocybin in this sample of pharmacy students. Findings from this study support reports from previous studies with healthcare students regarding psilocybin-assisted therapy and medical cannabis [25,[32][33][34]. This study also offers some insight into how pharmacy students think and feel about psilocybin as a treatment option, which could affect pharmacy education, and how psychedelic medications may be introduced into clinical settings in the future.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Specifically, greater self-assessed knowledge of psilocybin, more concern for possible negative effects from its use, and greater belief in the decriminalization of psilocybin for both recreational and therapeutic use were significant predictors of more positive attitudes about psilocybin in this sample of pharmacy students. Findings from this study support reports from previous studies with healthcare students regarding psilocybin-assisted therapy and medical cannabis [25,[32][33][34]. This study also offers some insight into how pharmacy students think and feel about psilocybin as a treatment option, which could affect pharmacy education, and how psychedelic medications may be introduced into clinical settings in the future.…”
Section: Discussionsupporting
confidence: 85%
“…The researchers of the current study have published reports about the perceptions of both medical cannabis and psilocybin-assisted therapy among medical students [25,[32][33][34]. However, little is known about pharmacy students' attitudes toward psilocybin, including their personal experiences with it.…”
Section: Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey used Likert-type items with a six-point response scale (1=strongly agree to 6=strongly disagree), categorical items, and yes/no questions. Many of the items were adapted from various published studies, mostly regarding the use of medical cannabis as no measures specific to medical psilocybin could be found [7,[24][25][26][27][28][29]. The content areas assessed are delineated below.…”
Section: The Instrumentmentioning
confidence: 99%
“…According to recent studies, young adults have a positive perception of CBD despite having limited knowledge of its evidence base or regulation [ 26 ]. Several studies have shown that the pharmacological knowledge of pharmacists, physicians, students, patients, and recreational users in other countries is insufficient regarding cannabis and cannabinoid-derived drugs [ 12 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. This study aimed to analyze the attitudes and knowledge of physicians, pharmacists, and students in Croatia about the therapeutic use of cannabis and cannabinoid-derived medicines.…”
Section: Introductionmentioning
confidence: 99%